Impact of intraday volatility on option pricing - Tomek, Pavel (2020)
This thesis provides an overview of existing theory of both introductory and more advanced volatility modelling and option pricing topics. GARCH model with various extensions and stochastic volatility models under Bayesian inference are dealt with in greater detail, spline extension for intraday volatility periodicity modelling in GARCH framework is suggested. The theory is exploited to estimate eleven different volatility model specifications for Euro Stoxx 50 index, two best performing models are selected. These models are used in Monte Carlo simulations for valuation of options on Euro Stoxx 50 index under the assumption of stochastic volatility. Impact of intraday volatility on theoretical option values is studied and isolated.